Analysis Of Factors Causing Moral Degradation Of Grade Vi Galang Bulan Students Seen From Hypothetical - Hesty Febrian Widyana; Alfina Alfina; Muhammad Isra; Lalu Sumardi (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
The purpose of this study was to analyse the factors causing moral degradation of grade VI students at SDN Galang Bulan, with a focus on the influence of the family environment, peers, school environment support, the times and technology, and the lack of character education programs. The method used was a qualitative approach with data collection techniques through interviews, participant observation, and focus group discussions. The results showed that family environment factors and peer influence have a significant impact on students' moral behaviour. In addition, support from the school environment and technological developments also contribute to moral degradation. The conclusion of this study emphasises the importance of collaboration between schools, parents and communities in creating an environment that supports the formation of good character in students.